Spread of Democracy by Pan European Movement: An Historical Overwiev - Ivanka D. Vasilevska Ivan, Stojanovski (Faculty of Law - Kicevo, University "St. Kliment Ohridski" - Bitola, 2019)
For the majority of Europeans, World War I meant the beginning of the end of the European civilization. The minority, however, drew the conclusion that Europe's capacity to react the war depended on its ability to overcome the aggressive nationalisms that had dragged the European continent into catastrophe and to adopt the ideal of a united and peaceful Europe as a common project...
Keywords: World War I, Richard Coudenhove-Kalergi, Paneurope, Paneuropean movement, Second World War.